German constitutional jurisdiction and fundamental rights (2011)
The fundamental rights inGermanyaredividedintosubjective publicrights andsimplyin dividual rights. The former are unchangeable because they are part of the essence of theGerman political systemand thelatter are oflegislative development. TheGerman Constitution has created constitutional institutionsto distinguishwhatisconstitutional of the regular,such as writ of protection, theconcrete and abstractcontrolof norms, whi chseeksto breakwith thepresumption ofconstitutionalityand legalityinlegal, adminis trativeandjudicial decisions.